Dor, limitação de atividades, mobilidade e funcionalidade entre mulheres após parto vaginal e cesárea - Moreira, Brenda Maia de Almeida (2024)
Introduction: The puerperium has its beginning soon after the end of childbirth, with the exit of the placenta, ending when all reproductive organs return to their non-pregnant state. Regardless of the type of delivery, reports of pain can occur in different locations and this is able to directly affect day-to-day activities and personal care. However, we seek to assess the existence of differences between women after vaginal delivery and cesarean section. Objectives: To compare pain, activity limitation and mobility in the immediate postpartum period, and to compare functionality in the late postpartum period among women after vaginal delivery and cesarean section. Methods: Cross-sectional analytical observational study conducted at the Assis Chateaubriand Maternity School (MEAC) of the Federal University of Ceará (UFC), Brazil, with postpartum women from 18 years of age. We evaluated sociodemographic and clinical data, obstetric history, as well as presence and intensity of pain (END), activity limitations and performed the mobility test Timed up and Go (TUG) between 12 and 48 hours postpartum. After 30 days, by telephone, the World Health Disability Assessment Schedule 2.0 (version 12 items) was applied to evaluate the functionality. In the statistical analysis we used the Chi-square test, Fisher’s exact test and T test (α=0.05), considering the significance level of 5%. Results: The sample consisted of 148 women, with a mean age of 28.5 years, (SD 6.3) years, of which 53.4% (n=79) had vaginal delivery and 46.6% (n=69) cesarean section. We observed an association of cesarean delivery with the presence of low back pain (p=0.03), abdomen (p<0.001) and lower limbs (p=0.01); and vaginal delivery with perineal pain (p=0.01). Cesarean section was associated with the presence of pain and limitation to sit, stand, walk (p<0.001), lie down (p=0.001) and bathe (p=0.02). Mobility, in the immediate postpartum period, and functionality, in the late postpartum period, did not differ between the types of delivery. Conclusion: Cesarean section is associated with higher frequency of pain in different regions of the body, as well as greater pain intensity and limitations for activities of daily living in the immediate postpartum, while perineal pain was associated with vaginal delivery. We emphasize the need for early care and monitoring of this population, preventing limitations in their activities.